The Sulfur Microbial Diet and Risk of Colorectal Cancer by Molecular Subtypes and Intratumoral Microbial Species in Adult Men. Issue 8 (1st August 2021) - Sikavi, Daniel R.; Nguyen, Long H.; Haruki, Koichiro; Ugai, Tomotaka; Ma, Wenjie; Wang, Dong D.; Thompson, Kelsey N.; Yan, Yan; Branck, Tobyn; Wilkinson, Jeremy E.; Akimoto, Naohiko; Zhong, Rong; et al.
Abstract : INTRODUCTION: We recently described the sulfur microbial diet, a pattern of intake associated with increased gut sulfur-metabolizing bacteria and incidence of distal colorectal cancer (CRC). We assessed whether this risk differed by CRC molecular subtypes or presence of intratumoral microbes involved in CRC pathogenesis ( Fusobacterium nucleatum and Bifidobacterium spp.). METHODS: We performed Cox proportional hazards modeling to examine the association between the sulfur microbial diet and incidence of overall and distal CRC by molecular and microbial subtype in the Health Professionals Follow-Up Study (1986–2012). RESULTS: We documented 1, 264 incident CRC cases among 48, 246 men, approximately 40% of whom had available tissue data. After accounting for multiple hypothesis testing, the relationship between the sulfur microbial diet and CRC incidence did not differ by subtype. However, there was a suggestion of an association by prostaglandin synthase 2 (PTGS2) status with a multivariable adjusted hazard ratio for highest vs lowest tertile of sulfur microbial diet scores of 1.31 (95% confidence interval: 0.99–1.74, P trend = 0.07, P heterogeneity = 0.04) for PTGS2-high CRC. The association of the sulfur microbial diet with distal CRC seemed to differ by the presence of intratumoral Bifidobacterium spp. with an adjusted hazard ratio for highest vs lowest tertile of sulfur microbial diet scores of 1.65 (95% confidence interval: 1.14–2.39, P trend = 0.01, P heterogeneity = 0.03) for Bifidobacterium -negative distal CRC. We observed no apparent heterogeneity by other tested molecular markers. DISCUSSION: Greater long-term adherence to the sulfur microbial diet could be associated with PTGS2-high and Bifidobacterium -negative distal CRC in men. Additional studies are needed to further characterize the role of gut microbial sulfur metabolism and CRC.